THE EFFECT OF TWO STAY TWO STRAY STRATEGY ON STUDENTS’ LISTENING COMPREHENSION - Rama dani (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The aims of the research are to know: 1)The extent of the application of two stay two stray strategy in teaching listening comprehension, 2) The extent of the students’ Listening Comprehension before and after using by two stay two stray strategy, 3) Whether any significant effect of two stay two stray on students listening comprehension . The population in this research is all of the tenth grade students of SMA Negeri 8 Padangsidimpuan which consist of 122 students. Sample were 24 students which taken by purposive sampling. The research method that used was experimental method. To collecting the data by observation sheet and multiple choice as an instrument. The mean score of the application Two Stay Two Stray was 3.5 categorized “Very Good”. To know the result of the data, the researcher analysis data by use the formula of ttest. The result of data analysis show that of ttest is 29.12 while ttable is 2.07. It means that ttest is higher than ttable. So, the hypothesis is accepted. In conclusion there is significant effect of Two Stay Two Stray Strategy on students’ listening comprehension at the tenth grade students of SMA Negeri 8 Padangsidimpuan.